Implementasi Sistem Informasi Akuntansi Dan Administrasi Berbasis Digital - Edi Triwibowo; Suriyanti Suriyanti; Dian Sulistyorini Wulandari; Aji Saputra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Villages have the opportunity to develop the potential they have had since the birth of the Law on Villages. Optimizing the potential of the village is used for the benefit of the village community. The aim of optimizing village potential is to improve the life of the village community. The aim of establishing Village-Owned Enterprises (BUMDes) is one of the government's efforts to stimulate the village economy. BUMDes is expected to become a locomotive for village economic movements that can improve the welfare and reduce poverty of village communities. In order for this goal to be achieved, BUMDes need to be managed professionally so that they can compete and develop well. BUMDes in Gandasari Village, Bekasi Regency. BUMDes receives full support from the local village government. BUMDesa Gandasari Village has limited human resource capabilities. The limitations of existing human resources are the ability to report financial results from operational activities carried out. The Community Partnership Program (PKM) aims to provide financial management methods that were previously manual to become systematic and digitalized. The output of the activities carried out is that BUMDes administrators understand the Bumdes administration system and accounting/bookkeeping and have the ability to create BUMDes Financial Reports in the form of simple accounting, namely creating daily cash books, balance sheets, profit and loss reports and systematic, digital-based capital change reports.